Local Wisdom Tri Hita Karana and Based on Indigenous Communities in Bali - I Wayan Gede Suacana; I Nyoman Wiratmaja; I Wayan Sudana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This article discusses how to develop ecotourism policy based on Balinese indigenous peoples accompanied by the value of local wisdom they have. Development that aims to have a positive impact on environmental conservation, local wisdom and cultural preservation of the local community. The method used In the first stage, primary and secondary data were collected. The second stage, choosing an approach to reviewing data. The third stage, analyze and interpret the data that has been selected. The fourth stage is to write and construct the results. The results of the study show that ecotourism with local wisdom Tri Hita Karana strongly emphasizes the integration of the three elements of Parahyangan, Pawongan, and Palemahan, none of which occupies a special portion. Opportunities and challenges for ecotourism with local wisdom of Tri Hita Karana and based on indigenous peoples in Bali are: maintaining the integration of the three elements in Tri Hita Karana namely Parahyangan, Pawongan, and Palemahan in ecotourism management so that no one occupies a special portion; keep the area sustainable as a natural area and still ensure environmental sustainability; ensure the preservation and utilization of species and their ecosystems; utilization of the environment for ecotourism using a conservation and utilization approach; encourage participation and improvement of community welfare in ecotourism management, including by involving them in decision making, management of tourism objects; environmental conservation education and the development of ecotourism potential, ranging from uniqueness, accessibility, facilities and governance.